The disappearance of land use from UNFCCC decisions: A guided topic analysis - Goldstein, K.; Rodrigues, B.; Jacobetty, P.; Hahn-Madole, K.; Jörgens, H.; Kolleck, N. (Land Use Policy, 2025)
The United Nations Framework Convention on Climate Change (UNFCCC) plays a pivotal role in shaping global environmental policies, yet a topic analysis of UNFCCC decisions reveals variations in the emphasis on distinct topics each year. This study critically examines all UNFCCC decisions from COP1 in 1995 to COP28 in 2023, along with decisions of the Kyoto Protocol and Paris Agreement. We utilize a form of Natural Language Processing called Guided Latent Dirichlet Allocation to examine how 16 topics that were predefined by the UNFCCC are represented within decisions. The results show how “Land Use”, a topic critical for climate change mitigation, is prominently featured only in certain years. Through network analysis, we illustrate land use’s limited cooccurrence with other topics within decisions and conferences. We draw on Punctuated Equilibrium and Policy Bubble theories to describe land uses’s broader geopolitical trends.